Analisis Sub-Struktur Menara BTS pada Area dengan Daya Dukung Tanah yang Rendah - Cahyono, Heru Setiyo; Arief, Lukman; Soedjarwoko, Endrik; Handini, Devi Ratna (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
The construction of BTS towers to fulfill equitable communication requires analysis of structural construction calculations so the tower can be standing properly in locations that have low soil bearing capacity. This research aims to analyze the design of the BTS tower sub-structure to withstand in structural loads, wind, overturning, and uplift forces so the tower can be standing properly. To achieve the research objectives, studies and analyses were conducted through literature study, load analysis, structural modeling through software analysis and interaction diagrams, evaluation of soil bearing capacity, and verification of applicable construction standards in Indonesia. The analysis shows the dead load of the sub-structure, the overturning moment of 6.539 x 10³ kN.m in the X direction and 5.352 x 10³ kN.m in the Y direction meet the safety value of 1, thus ensuring stability according to SNI 8460: 2017. The maximum ground pressure is 97,808 kN/m², below the required 294,200 kN/m² at a depth of 1.4 m, with safety factors of soil bearing capacity (3.008), shear capacity (2.897), and shear strength (1.5) all meeting safety standards. The reinforcement analysis follows SNI 03: 2847-2019, specifying that D16-200 reinforcement is required for bottom and top with a ratio of 0.002 and 0.001. Torsional shear for axial (1,225 x 10³ kN.m) and compression (1,578 x 10³ kN.m) stress conditions, as well as ratios exceeding 1% ensure the safety of the support. Overall all structural elements meet the safety requirements, ensure the stability of the tower and comply with relevant standards.